กระบวนการเรียนการสอนเพื่อส่งเสริมความสามารถในการสร้างสรรค์ดนตรีไทยสำหรับนักเรียน ระดับมัธยมศึกษาตอนต้น: การถอดบทเรียนจากศิลปินแห่งชาติ สาขาศิลปะการแสดง (ดนตรีไทย) - ศาสตรา, อุทัย; ตรีวรัญญู, ชาริณี; ฉัพพรรณรัตน์, ยุทธนา (Journal of Education Studies, Chulalongkorn University, 2019)
This research aimed to 1) study and develop an instructional process for promoting ability in Thai music creativity for lower secondary students based on using the knowledge of lessons learned from national artists in performing arts (Thai Music), and 2) study the effects of using the developed instructional process. The research procedures were conducted in four phases. In phase 1, the lesson focused on promoting abilities in Thai music creativity from five national artists; in phase 2, an instructional process was developed; in phase 3, the effects of developing an instructional process were studied, during which 35 ninth-grade students at Chulalongkorn University Demonstration Secondary School comprised the subjects; and in phase 4, the completed instructional process as the final loop of this research was proposed. The data were analyzed by using data interpretation and induction, and the statistics were used for data analysis including the mean, standard deviation, and comparison using the data by t-test. The findings were as follows: 1) the developed instructional processes consisted of two phases, namely Phase 1, which prepared for Thai music creativity in two sub-steps: (1) practicing the melody of Thai traditional songs, and (2) developing basic knowledge for Thai music creativity; in phase 2, the ability in Thai music creativity was developed in four sub-steps: (1) learning the creativity of Thai music melodies from modeling, (2) practicing the creativity of Thai music melodies, (3) enhancing the experiences of Thai music creativity, and (4) developing the product of Thai music creativity. 2) The results demonstrated that after implementing the developed instructional process, the students’ ability in Thai music creativity scores were significantly higher than the pretest scores at a .05 level, and students' development of the ability in Thai music creativity were significantly improved, especially the ability to create Thai musical melodies fluently and appropriately.